Experimental study on cyclic simple shear behaviour of predominantly dilative silica sand. Issue 1 (2nd January 2023) - Baghbani, Abolfazl; Costa, Susanga; O'Kelly, Brendan C; Soltani, Amin; Barzegar, Milad
ABSTRACT: This study investigated the cyclic behaviour of a severe dilative silica sand from Rudsar, Northern Iran, through simple shear tests. For this purpose, monotonic (constant volume/vertical stress) and cyclic (constant vertical stress) tests were performed on moist sand specimens prepared at initial relative densities of 20–60%, vertical stresses of 100–300 kPa, and cyclic stress ratios of CSR = 0.20, 0.25 and 0.30. These also included bender element tests to determine the small-strain shear modulus G max . An increase in initial relative density, vertical stress and number of loading cycles led to a nonlinear increase in the secant shear modulus G sec, while the opposite was observed for increasing CSR. Moreover, increasing CSR improved the damping ratio, whereas increasing the initial relative density, vertical stress and/or number of loading cycles had negative effects on the damping ratio. Finally, the bender element test results showed that G max increased for increasing vertical stress and initial relative density.